2010
DOI: 10.1260/1475-472x.10.1.17
|View full text |Cite
|
Sign up to set email alerts
|

A Weak-Scattering Model for Turbine-Tone Haystacking outside the Cone of Silence

Abstract: We consider the scattering of sound by turbulence in a jet shear layer. The turbulent, time-varying inhomogeneities in the flow scatter tonal sound fields in such a way as to give spectral broadening, which decreases the level of the incident tone, but increases the broadband level around the frequency of the tone. The scattering process is modelled for observers outside the cone of silence of the jet, using high-frequency asymptotic methods and a weak-scattering assumption. An analytical model for the far-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…some of the energy in the tone is scattered into adjacent frequency bands, but the total remains constant, then the out-of-flow microphones can be used to determine one-third octave band levels with good accuracy. Candel et al 10 gives some support for that assumption, at least for weak haystacking (Powles et al 11 ) where the scattered energy is small compared to that in the tone, but we are not aware of any theoretical or experimental proof that this is true in general. Figure 9, compares PWL measurements made using a representative microphone from the inflow traverse (black) and the out-of-flow fly-over array (red).…”
Section: Figure 8 Measured (Black) and Background (Green) Pwls Out-mentioning
confidence: 80%
“…some of the energy in the tone is scattered into adjacent frequency bands, but the total remains constant, then the out-of-flow microphones can be used to determine one-third octave band levels with good accuracy. Candel et al 10 gives some support for that assumption, at least for weak haystacking (Powles et al 11 ) where the scattered energy is small compared to that in the tone, but we are not aware of any theoretical or experimental proof that this is true in general. Figure 9, compares PWL measurements made using a representative microphone from the inflow traverse (black) and the out-of-flow fly-over array (red).…”
Section: Figure 8 Measured (Black) and Background (Green) Pwls Out-mentioning
confidence: 80%
“…These configurations have also been studied analytically by Campos 5,6 who concluded that for an engine jet, widening the shear layer could significantly reduce tonal components propagating through the exhaust. Powles et al 25 and McAlpine et al 22 developed an analytical model to predict the haystacking of turbine tones. This model is able to consider frozen or evolving turbulence, and the variations of the source/flow parameters show behaviors of the spectra agreeing with existing experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent shift of source position at the scattered frequencies has not been investigated in detail before and is compared here with that obtained from the weak scattering relationship derived by Cargill, as noted by Powles et al 4 .…”
Section: Comparison Of Experimental Beamformer Results With Weak mentioning
confidence: 83%
“…The objective was to improve our understanding of the tone haystacking mechanisms with the aid of beamforming and the weak scattering theory proposed by Cargill 3 , as extended by Powles et al 4 and McAlpine et al 5 . Part II describes that experiment, Part III presents an analysis of the far-field and the beamformer data and Part IV describes a comparison of one aspect of the Cargill theory with the observations extracted from the processed beamformer data.…”
Section: Introductionmentioning
confidence: 99%